Towards the transit-oriented region: Polycentric urbanism to transform automobile dependent cities - Hendrigan, Cole Evan (Curtin University, 2014)
Following from the rhetoric and promise of compact cities, how best may we accurately model the interactions of local land-use plans with public transportation provision to transform automobile-dependent metropolitan regions? The research aims to uncover the capacity for redevelopment to achieve a long-ranged transformation to a Transit-Oriented Region. The results reveal a methodology to understand metropolitan growth as a science, to better inform the art of human-scaled urban design.